Antyk w literaturze anglo-normandzkiej w XII wieku - Abramowicz, Maciej (Studia Europaea Gnesnensia, 2012)
The aim of the article is to present a new phenomenon in medieval culture, namely the appearance of versions of ancient narratives, delivered in old French, in the circles of anglo-norman culture. Their appearance is a response to the need to elevate the prestige of monarchy and introducing new, lay knightly elites into the circles of the higher culture.